2010
DOI: 10.1002/ppul.21295
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal influences of asthma and obesity on lung function testing, ahr, and airway inflammation in prepubertal children

Abstract: Although asthma and obesity are among the major chronic disorders their reciprocal or independent influences on lung function testing, airways hyperresponsiveness (AHR) and bronchial inflammation has not been completely elucidated. In 118 pre-pubertal Caucasian children anthropometric measurements functional respiratory parameters (flow/volume curves at baseline and after 6-minute walk test [6MWT]) together with bronchial inflammatory index (FeNO) were assessed. The study population was divided into four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
2
21
0
3
Order By: Relevance
“…Further, controller medication use may have also contributed to or obesity have demonstrated a similar lack of association. 37 Other pediatric studies that demonstrated a correlation between PFTs and adiposity included adolescents, raising the question as to whether change in body fat distribution occurring during adolescence may have played a role 38 and may provide an explanation for the discordance between pediatric Although the infl ammatory pattern in obese asthmatic children did not differ from that in obese nonasthmatic children in our study, several factors can be hypothesized for the occurrence of asthma in some, but not all, obese children. The pattern of fat distribution may play a role, because central adiposity has been associated with asthma in children.…”
Section: Discussionmentioning
confidence: 63%
“…Further, controller medication use may have also contributed to or obesity have demonstrated a similar lack of association. 37 Other pediatric studies that demonstrated a correlation between PFTs and adiposity included adolescents, raising the question as to whether change in body fat distribution occurring during adolescence may have played a role 38 and may provide an explanation for the discordance between pediatric Although the infl ammatory pattern in obese asthmatic children did not differ from that in obese nonasthmatic children in our study, several factors can be hypothesized for the occurrence of asthma in some, but not all, obese children. The pattern of fat distribution may play a role, because central adiposity has been associated with asthma in children.…”
Section: Discussionmentioning
confidence: 63%
“…However, since all asthmatics had ER visits with or without hospitalizations for asthma exacerbations for several years prior to study participation, irrespective of obesity status, we do not believe that there was a misclassification bias based on our selection criteria. Moreover, we did not perform spirometry testing after completion of the 6MWT, which could have elucidated exercise induced pulmonary function changes and hence differences between the four study groups, as recently reported in a Caucasian pre‐pubertal population 33. Further, the relatively small sample, particularly in the normal‐weight asthmatic group, may have played a role in the borderline significance of some associations.…”
Section: Discussionmentioning
confidence: 92%
“…We recognize that 6MWT has not been routinely used to measure functional exercise capacity among children. However, recent studies19, 28, 33 have increasingly utilized it given the ease of its application in clinical settings. While correlating closely with the results of maximal exercise testing,19 it obviates the need for specialized testing equipment and trained personnel required for exercise testing.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them reported results for persons with asthma, with one finding no association [14] and the other a negative association [15]. Several other more recent studies have issued similarly inconsistent findings [18][19][20].…”
Section: Introductionmentioning
confidence: 82%